2021
DOI: 10.1016/j.numecd.2021.08.030
|View full text |Cite
|
Sign up to set email alerts
|

High glomerular filtration rate is associated with impaired arterial stiffness and subendocardial viability ratio in prediabetic subjects

Abstract: Background and aims: High glomerular filtration rate (HGFR) is associated with cardiovascular damage in the setting of various conditions such as obesity and diabetes. Prediabetes was also associated with increased GFR, however, the association between prediabetes, HGFR and cardiovascular damage has not been investigated. In this study, we investigated the association between HGFR and early markers of cardiovascular disease in subjects with prediabetes. Methods and results: Augmentation pressure (Aug), augment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Pulse wave velocity . The SphygmoCor CvMS (AtCor Medical, Sydney, Australia) system was used for the determination of the pulse wave velocity (PWV), as previously described [ 28 ]. This system uses a tonometer, and two different pressure waves obtained at the common carotid artery (proximal recording site) and at the femoral artery (distal recording site).…”
Section: Methodsmentioning
confidence: 99%
“…Pulse wave velocity . The SphygmoCor CvMS (AtCor Medical, Sydney, Australia) system was used for the determination of the pulse wave velocity (PWV), as previously described [ 28 ]. This system uses a tonometer, and two different pressure waves obtained at the common carotid artery (proximal recording site) and at the femoral artery (distal recording site).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies, however, highlight the presence of altered values of arterial stiffness parameters in diabetic patients. Di Pino et al [ 43 ] have shown that patients with prediabetes and high glomerular filtration rate values have increased augmentation pressure and AIx values and reduced SEVR values ( p < 0.05). In patients with type 1 diabetes mellitus, reduced SEVR values correlate independently and negatively with the presence and degree of microalbuminuria and are a superior predictor of PWV in assessing the albumin excretion rate [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent clinical trial, the same group of investigators demonstrated that chronic kidney disease patients with an SEVR of less than 130% were associated with a 16-fold increased risk of fatal cardiovascular events compared to patients with an SEVR greater than 130% ( p = 0.004) [ 46 ]. Not only do low eGFR values correlate with SEVR, but high ones do as well, with the main determinants of SEVR in the prediabetic population being SBP, eGFR and insulin resistance as major determinants of arterial stiffness [ 43 ]. Based on the concept that a significant percentage of hypertensive patients are associated with peripheral arterial disease, the analysis of paraclinical parameters of arterial stiffness has prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The classic description of DKD involves progressive stages of glomerular hyperfiltration, microalbuminuria, overt proteinuria, and a decline in the estimated glomerular filtration rate (eGFR), eventually leading to dialysis [3,4]. In the last few years, this concept has been increasingly challenged as evidence suggests that DKD in the contemporary era presents in a more heterogeneous manner.…”
Section: Non-albuminuric Phenotype: Clinical Presentation Epidemiolog...mentioning
confidence: 99%